Clinical validation of a real-time polymerase chain reaction assay for rapid detection of Acinetobacter baumannii colonization. Issue 1 (September 2016) - Blanco-Lobo, P.; González-Galán, V.; García-Quintanilla, M.; Valencia, R.; Cazalla, A.; Martín, C.; Alonso, I.; Pérez-Romero, P.; Cisneros, J.M.; Aznar, J.; McConnell, M.J.
Summary: Real-time polymerase chain reaction (PCR)-based approaches have not been assessed in terms of their ability to detect patients colonized by Acinetobacter baumannii during active surveillance. This prospective, double-blind study demonstrated that a real-time PCR assay had high sensitivity (100%) and specificity (91.2%) compared with conventional culture for detecting A. baumannii in 397 active surveillance samples, and provided results within 3 h. Receiver-operator curve analyses demonstrated that the technique has diagnostic accuracy of 97.7% (95% confidence interval 96.0–99.3%). This method could facilitate the rapid implementation of infection control measures for preventing the transmission of A. baumannii .